Ductus arteriosus. Advanced differentiation of smooth muscle cells demonstrated by myosin heavy chain isoform expression in rabbits. - H S Kim; Masanori Aikawa; Kenjiro Kimura; Makoto Kuro‐o; Ken‐ichi Nakahara; Toru Suzuki; Hirotaka Katoh; E Okamoto; Y Yazaki; R Nagai (1993)
BACKGROUND The closure of the ductus arteriosus (DA) is one of the most striking cardiovascular events that occur at birth. It has been attributed to oxygenation and intrinsic prostaglandins. However, selective constriction of DA suggests the presence of highly specialized contractile mechanisms in DA. We previously reported that smooth muscle myosin heavy chain isoforms, SM1 and SM2, are molecular markers for smooth muscle differentiation because of their unique expression pattern during vascular development. SM1 and SM2 are generated from a single gene through developmentally regulated alternative RNA splicing; SM1 is expressed in almost all stages of differentiation of the vascular smooth muscles, but SM2 is found only after birth. METHODS AND RESULTS Immunohistochemistry was performed to study the expression of the different types of myosin heavy chain isoforms in DA of fetal and neonatal rabbits. Electron microscopic examinations were also carried out to demonstrate ultrastructural characteristics of ductus muscles. We found that SM2 is expressed before birth in the medial layer of DA, indicating advanced differentiation of smooth muscle cells in DA. The exact location of immunoreactivity for SM2 was in the smooth muscle cell of the medial layer of DA. Immunoreactivity for SM1, however, was not different for DA and adjacent great arteries. Transmission electron microscopy demonstrated greater amounts of myofilaments in medial smooth muscles of DA than those of aorta. CONCLUSIONS These results indicate that smooth muscles in DA are more differentiated than those in other arteries, which may be one of the cellular mechanisms responsible for the unique closure of DA at birth.